Competitiveness Comparative Research on Jiaozuo Service Industry Based on Synchronic and Diachronic Data - XU Jun (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Service industry plays a more and more important role in economic development, it had become an important symbol for the enhancement of one region competitiveness. The paper constructed the Jiaozuo service competitive evaluation model, which used 2004-2011 years sequence data of Jiaozuo and synchronic data of Zhengzhou, Kaifeng, Luoyang, Xinxiang, Jiaozuo five cities, based on the DEA method, designed input index including employees and fixed assets, designed output index including service industry output value and growth rate, then it solved the answer with LINGO8.0 linear programming software. Model could not only evaluate sequence change on development of service industry competitiveness for eight years in Jiaozuo, but also did a horizontal section comparison with Zhengzhou, Kaifeng, Luoyang, Xinxiang four Cities. Model operation results showed that Jiaozuo service industry appeared to be on the mend but unstable situation on the overall effectiveness according to the longitudinal input and output, the horizontal section comparing showed that it had slightly shortage than Zhengzhou, Kaifeng city, it was in a horizontal line with Xinxiang, Luoyang, but the total amount was insufficient, it was totally in accord with the actual situation in Jiaozuo service industry development. Finally, it proposed the countermeasure and suggestion from Jiaozuo important development industries, service industry development policy and talent training. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2514